Ropivacaine 0.25% versus bupivacaine 0.25% in immediate post tonsillectomy pain management: a randomised control trial - Nasser, Arfan; U. P., Santosh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Tonsillectomy is one of the most common surgeries performed by an otolaryngologist, with post operative pain during the initial 24 hours being one of the most common challenging concerns. This makes it a need to find a suitable mode for managing the post operative pain imperative. This study aims to: assess the post operative pain control with ropivacaine 0.25% and bupivacaine 0.25% and to assess which among these two drugs are better in controlling the post operative pain and safer. Methods: The 70 patients were selected, randomized, double blinded into group 1 and group 2 and given intraoperative infiltration of either 0.25% ropivacaine or 0.25% ropivacaine respectively into the tonsillar bed after tonsillectomy. The surgeries were done by the same surgeon by cold steel method of tonsillectomy. Post operative pain was evaluated using VAS (visual analogue scale) at regular intervals. Other parameters like hemodynamic status, surgical duration, any adverse reactions to the medications are also recorded. Results: There was a statistically significant difference seen in the post operative pain scores between the two groups at all time intervals, with group 1 having a lower score compared to group 2. Conclusions: Intraoperative infiltration of local anesthetics into the tonsillar bed was effective in controlling the post operative pain, with ropivacaine suitable anesthetic agent as compared to bupivacaine due to its higher efficacy and safety.